2023
DOI: 10.28991/cej-2023-09-03-04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polypropylene Fibers on Swelling Potential and Shear Strength of Clay

Abstract: Expansive clays can cause major problems for urban development (roads, railways, infrastructure, etc.); therefore, reducing the swelling potential of clays has always been a concern in the geotechnical field. The presented paper investigates the effect of polypropylene reinforcement fibers on the swelling potential and shear strength of clay. The samples studied were taken from the clayey region of Mila, located in the northern east of Algeria. The experimental procedure adopted in this research consists first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The findings of the PPF's soaking and drying phases demonstrated that, with repeated cycles, the influence of PPF continues to reduce swelling, and that PPF's 2% generates a lower ratio of swell to shrink, achieving an improvement factor of swell and shrink that is higher than 57%. The impact of polypropylene reinforcing fibers on the potential for swelling and shear resistance of soft soil is examined in the study by Yacine et al [39]. The first step in the experimental protocol used in this study is to evaluate the soil samples' mechanical, mineralogical, and physical properties without the use of reinforcement.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the PPF's soaking and drying phases demonstrated that, with repeated cycles, the influence of PPF continues to reduce swelling, and that PPF's 2% generates a lower ratio of swell to shrink, achieving an improvement factor of swell and shrink that is higher than 57%. The impact of polypropylene reinforcing fibers on the potential for swelling and shear resistance of soft soil is examined in the study by Yacine et al [39]. The first step in the experimental protocol used in this study is to evaluate the soil samples' mechanical, mineralogical, and physical properties without the use of reinforcement.…”
Section: Resultsmentioning
confidence: 99%